2006
DOI: 10.2174/156720206775541732
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Delimitation of the Infarct Zone by Capillary-Derived Nestin- Positive Cells in Aged Rats

Abstract: An important cellular event associated with reduced structural and functional recovery after stroke in aged animals is the early formation of a scar in the infarcted region that impairs neural recovery and repair. Despite the detrimental impact of infarct scar formation, the brain regions and cell types that supply the components of the scar are not well characterized. We hypothesized that premature cerebral scar formation in aged animals is associated with an altered cellular response to cerebral ischemia. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…A growing body of evidence suggests that inflammatory processes are involved in the pathophysiology of stroke (Badan et al, 2003;Danton and Dietrich, 2003;Popa-Wagner et al, 2006;Price et al, 2006). Following ischemic stroke, microglia and astrocytes show both an increase in number as well as a strongly reactive phenotype in the infarcted region (Badan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that inflammatory processes are involved in the pathophysiology of stroke (Badan et al, 2003;Danton and Dietrich, 2003;Popa-Wagner et al, 2006;Price et al, 2006). Following ischemic stroke, microglia and astrocytes show both an increase in number as well as a strongly reactive phenotype in the infarcted region (Badan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Work in our laboratory and in others has demonstrated that the period from days 3-14 poststroke is important in the inflammatory reaction that is a hallmark of the pathophysiology of stroke. This is also a critical period for interventions, if they are to successfully promote functional recovery (Danton and Dietrich, 2003;Fisher and Henninger, 2007;Popa-Wagner et al, 2006. This time-frame, therefore, is a logical focus for efforts (such as those suggested by Wahlgren and Ahmed) aimed at understanding basic mechanisms of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after stroke, nestin- and GFAP-positive cells demarcated the infarct core significantly earlier in aged rats than in young rats [79]. Proliferating astrocytes led to the premature glial scar formation in aged rats that presumably limits neurological recovery.…”
Section: Challenges For Neurorestorative Therapiesmentioning
confidence: 99%
“…The NSS decreased after treatment with Ilexonin A, suggesting that IA improves the recovery of neurological functions. Nestin-positive cells begin to accumulate in the peri-ischemic regions at d 1 after the stroke in the control and IA groups, in thread-like structures emanating from blood vessels or "budding" from capillary ends [20]. Unlike the control and IA groups, in the normal and sham groups, there were only few Nestin-positive cells, which marked microvascularization.…”
Section: Discussionmentioning
confidence: 94%